2019
DOI: 10.1021/acsnano.9b03660
|View full text |Cite
|
Sign up to set email alerts
|

Multilamellar Vaccine Particle Elicits Potent Immune Activation with Protein Antigens and Protects Mice against Ebola Virus Infection

Abstract: Recent outbreaks of emerging infectious diseases, such as Ebola virus disease (EVD), highlight the urgent need to develop effective countermeasures, including prophylactic vaccines. Subunit proteins derived from pathogens provide a safe source of antigens for vaccination, but they are often limited by their low immunogenicity. We have developed a multilamellar vaccine particle (MVP) system composed of lipid−hyaluronic acid multi-cross-linked hybrid nanoparticles for vaccination with protein antigens and demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…A lipid and biopolymer hybrid nanoparticle was investigated for the subcutaneous delivery of the Ebola virus spike glycoprotein [81]. The hybrid nanoparticles consisted of various lipids, including 1,2-dioleoyloxy-3-(trimethylammonium) propane, 1,2-dioleoyl-sn-glycero-3-phosphocholine, and maleimide-functionalized N-(4-carboxybenzyl)-N,N-dimethyl-2,3-bis(oleoyloxy)propan-1-aminium, which were crosslinked with thiolated hyaluronic acid.…”
Section: Nanovaccines Against Ebolamentioning
confidence: 99%
“…A lipid and biopolymer hybrid nanoparticle was investigated for the subcutaneous delivery of the Ebola virus spike glycoprotein [81]. The hybrid nanoparticles consisted of various lipids, including 1,2-dioleoyloxy-3-(trimethylammonium) propane, 1,2-dioleoyl-sn-glycero-3-phosphocholine, and maleimide-functionalized N-(4-carboxybenzyl)-N,N-dimethyl-2,3-bis(oleoyloxy)propan-1-aminium, which were crosslinked with thiolated hyaluronic acid.…”
Section: Nanovaccines Against Ebolamentioning
confidence: 99%
“…Moon et al demonstrated that when PLGA conjugated-malaria antigen, VMP001, was encapsulated within lipid membrane, these PLGA-lipid nanoparticles elicited higher humoral responses in vivo with 10-fold less amount of soluble protein vaccine dose and sustained similar antibody titers for up to 180 days [46]. Similarly, a lipid-polymer hybrid multilamellar vaccine particle (MVP), composed of cationic lipidhyaluronic acid, crosslinked with Ebola virus (EBOV) glycoprotein, generated long-lasting antigen-specific CD8+ and CD4+ T cell responses, and a single dose of MVP vaccination protected 80% of mice against EBOV infection [18].…”
Section: Polymeric Nanoparticlementioning
confidence: 99%
“…have also expanded on the ICMV strategy and developed lipid–polymer hybrid multilamellar vaccine particles (MVP) to incorporate Ebola virus antigen as well. [ 164 ] In this case, MVP immunization generated strong and durable antigen‐specific antibody and immune cell responses in mice, and single‐dose immunization protected 80% of mice from lethal Ebola virus infection. By contrast, an ICMV‐based vaccine only protected 40% of mice and the difference in vaccine‐mediated immune protection was suggested to arise from the greater antigen‐specific T cell response elicited by the MVP vaccine.…”
Section: Virus‐mimicking Nanoparticle Vaccinesmentioning
confidence: 99%